2021
DOI: 10.1007/s11356-021-16155-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various chemical compounds for the removal of SO2 and NOx with wet scrubbing for marine diesel engines

Abstract: Seawater, NaOH, NaClO, NaClO2, H2O2, and KMnO4 were used as scrubbing liquids to react with SOx and NOx separately in a customized wet scrubber. The absorption of SO2 in the aqueous phase was influenced by three factors: pH, ionic concentration, and oxidation potential. For NOx removal, the effectiveness of various chemical compounds can be ranked from least to most effective as follows: seawater, NaOH, H2O2 < NaClO < KMnO4 < NaClO2. This effectiveness was influenced by the chemical compound’s ability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…When the initial pH was 2.00, 2.50, 3.00, and 3.50, the maximum NO 2 concentration was 205 ppmv, 182 ppmv, 195 ppmv, and 135 ppmv, respectively. Chin et al [ 65 ] and Brogren et al [ 66 ] explained that 60−80% of the NO 2 generated in the reaction can be removed by Equations (18)–(22).…”
Section: Resultsmentioning
confidence: 99%
“…When the initial pH was 2.00, 2.50, 3.00, and 3.50, the maximum NO 2 concentration was 205 ppmv, 182 ppmv, 195 ppmv, and 135 ppmv, respectively. Chin et al [ 65 ] and Brogren et al [ 66 ] explained that 60−80% of the NO 2 generated in the reaction can be removed by Equations (18)–(22).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that oxidation potential of NaClO solution increased with solution pH decreasing from 11 to 6. As the pH of NaClO solution was maintained at 6 during the scrubbing process, the oxidation potential of NaClO solution was kept at a high level, which was not conducive to the hydrolysis absorption of NO 2 . It was possibly due to the relatively strong oxidation property of NaClO.…”
Section: Resultsmentioning
confidence: 99%
“…As the aqueous solubility of NO 2 was much higher than that of NO, part of NO 2 would be absorbed and generate NO 2 – , which could be oxidized to NO 3 – rapidly during the wet scrubbing process. However, due to the high flue gas flow rate and temperature, especially the scrubbing solution pH was kept at 6 and high oxidation of HClO was not conducive to the absorption of NO 2 , parts concentration of NO 2 may be released and caused NO oxidation rate higher than NO x removal efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, NO needs to be oxidized first before wet removal. Oxidizing NO to make it soluble in water, various oxidants have been investigated for their effectiveness in NO x removal. Among these oxidants, Na 2 S 2 O 8 has been widely used in the removal of organic toxic gases, treatment of organic contaminants in groundwater, and remediation of diesel-contaminated soil for its high stability, low cost, environmental friendliness, and good oxidation properties.…”
Section: Introductionmentioning
confidence: 99%